Bargaining positions in business e-negotiation - Tangpijaikul, Montri (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The study explores the context in which interactional metadiscourse markers in English are used in business email negotiation. Occurrences of these linguistic devices are shown in comparative frequencies supplemented with data from written observations and interviews with a company manager to observe the dynamics of business interaction and buyer-seller relationships which vary across time and stages throughout the course of e-negotiations. Findings reveal that the interpersonal linguistic features that realize personal engagement and attitude are common and frequently found in the middle of the negotiation when the business relationship is at stake while self-mentioning is commonly found with the purpose of solving logistics problems in the final shipping stage. This paper argues that interactional devices should not be viewed in time dimension alone but contexts in which they are used.